Differences in Admission Blood Pressure Among Causes of Intracerebral Hemorrhage. Issue 2 (February 2020) - Lin, Jessica; Piran, Pirouz; Lerario, Mackenzie P.; Ong, Hanley; Gupta, Ajay; Murthy, Santosh B.; Díaz, Iván; Stieg, Philip E.; Knopman, Jared; Falcone, Guido J.; Sheth, Kevin N.; Fink, Matthew E.; et al.
Abstract : Background and Purpose—: It is unknown whether admission systolic blood pressure (SBP) differs among causes of intracerebral hemorrhage (ICH). We sought to elucidate an association between admission BP and ICH cause. Methods—: We compared admission SBP across ICH causes among patients in the Cornell Acute Stroke Academic Registry, which includes all adults with ICH at our center from 2011 through 2017. Trained analysts prospectively collected demographics, comorbidities, and admission SBP, defined as the first recorded value in the emergency department or on transfer from another hospital. ICH cause was adjudicated by a panel of neurologists using the SMASH-U criteria. We used ANOVA to compare mean admission SBP among ICH causes. We used multiple linear regression to adjust for age, sex, race, Glasgow Coma Scale score, and hematoma size. In secondary analyses, we compared hourly SBP measurements during the first 72 hours after admission, using mixed-effects linear models adjusted for the covariates above plus antihypertensive agents. Results—: Among 484 patients with ICH, admission SBP varied significantly across ICH causes, ranging from 138 (±24) mm Hg in those with structural vascular lesions to 167 (±35) mm Hg in those with hypertensive ICH ( P <0.001). The mean admission SBP in hypertensive ICH was 17 (95% CI, 11–24) mm Hg higher than in ICH of all other causes combined. These differences remained significant after adjustment for age, sex, race, Glasgow Coma Scale score, and hematoma size ( P <0.001), and this persisted throughout the first 72 hours of hospitalization ( P <0.001). Conclusions—: In a single-center ICH registry, SBP varied significantly among ICH causes, both on admission and during hospitalization. Our results suggest that BP in the acute post-ICH setting is at least partly associated with ICH cause rather than simply representing a physiological reaction to the ICH itself. Abstract : Supplemental Digital Content is available in the text.